Adhesion GPCRs in nervous system development and disease - Langenhan, Tobias (Henry Stewart Talks, 2019)
Introduction into the adhesion GPCR family, Molecular layout of adhesion GPCRs, Adhesion GPCRs as putative mechanosensors, Models on adhesion GPCR activation and signaling, Developmental roles of adhesion GPCRs in the nervous system, Adhesion GPCR dysfunction in neuropsychiatric diseases